The Prevalence of Shoulder Pain in Elite Level British Swimmers and the Effects of Training Technique - Pollard, B. (2001)
The aim of the study was to determine the prevalence of interfering shoulder pain in a representative sample of elite level British swimmers. The study sought to determine how shoulder pain levels maybe influenced by specific training methods used by these athletes. 120 questionnaires were sent to four swimming clubs, requesting information on training methods. The questionnaires also requested information relating to the presence of shoulder pain, both past and present and any `aggravating` factors perceived by the respondent. A response rate of 88% was obtained. The current prevalence of shoulder pain was found to be 18% (age group swimmers) and 35% (senior swimmers). Chi-square analysis demonstrated that metres swum per week and shoulder pain showed statistical significance (p=0.001). Those athletes training higher distances were more likely to be suffering from shoulder pain. Chi-square analysis also revealed that percentage of freestyle swum per session and shoulder pain showed statistical significance (p=0.001). Those athletes swimming more freestyle per session were also more likely to have shoulder pain. Furthermore swimmers perceived that existing shoulder pain was aggravated by using hand paddles, doing weights, increasing distance swum and kicking with a board.